Germinação e vigor de sementes de soja em função da disponibilidade hídrica do solo e presença de Phomopsis sojae - Simoni, Fabiana De [UNESP] (2007)
The objective of the present research was to verify the effect of water availability and Phomopsis sojae in the germination of soybean seeds. For characterization of physiological and sanitary qualities of the seeds the following tests were used: germination and vigor (accelerated aging, bulk electric conductivity and dry mass of seedlings) and blotter test ; besides, it was determined the water content, before and after the aging. For the study of the emergence with water availability, three treatments were considered: 60% (H1), 40% (H2) and 20% (H3) of its water retention capacity. The seeds were artificially inoculated with Phomopsis sojae by contact with the fungi for a period of 32 hours, laterly they were sowed in plastic boxes for the emergence test with water availability. Four varieties (MSoy 8400, MSoy 8200, Embrapa 48 and Paradise) were seeded combined with three levels of water availability and the fungi, constituted 24 treatments with four replications. Each box received 50 seeds, these were maintained in laboratory. The evaluation of the seedlings emergence was made in 10th day after seeding and at the end of that period was made the evaluation of the soybean seedlings dry mass. For the study of the water availability in soybean seedlings and the levels of inoculation of the seeds with P. sojae were considered 18 treatments (3 water availability: 50% (H1), 40% (H2) and 30% (H3) of its water retention capacity x 6 levels of inoculated seeds (0, 5, 10, 20, 40 and 60%). The period of the seeds inoculation was the same used previously. The evaluation of the seedlings emergence was made in 10th day after the seeding and at the end of that period was made the evaluation of the soybean seedlings dry mass. The obtained results allowed to conclude that the relationship between the emergence of soybean seedlings in soil and Phomopsis sojae varied with the level of water...(Complete abstract, click electronic access below)